1981
DOI: 10.1111/j.1399-0004.1981.tb00695.x
|View full text |Cite
|
Sign up to set email alerts
|

Orbital cyst in addition to congenital cerebral and focal dermal malformations: A new entity?

Abstract: Two patients with similar congenital malformations, consisting of orbital cyst, cerebral malformations and focal dermal hypo‐ and aplasia are described. There is some similarity to the Goltz and Goldenhar syndromes; however, the delineation of a new entity or syndrome seems possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0
1

Year Published

1984
1984
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(27 citation statements)
references
References 3 publications
3
23
0
1
Order By: Relevance
“…The orbital findings of microphthalmos associated with intraorbital cyst are in accordance with previous observations (De Cock and Merizian, 1992). The orbital cysts were described as dermoid cysts (Tambe et al, 2003), orbital encephalocele (Moog et al, 1997), cysts with neuroepithelial hamartous structure (Bleeker-Wagemakers et al, 1990), cyst wall formed by neuroepithelium and glial tissues (De Cock and Merizian, 1992), vestigeal epithelial tissues of the retina (Dolfus et al, 1968), harmartomous with primitive glial and neuroepithelial structures (Wilson et al, 1985), hamartoma (Delleman and Oorthuys, 1981) or have not been specified. Based on the MR signal properties of the cyst in the present case a dermoid could be excluded.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The orbital findings of microphthalmos associated with intraorbital cyst are in accordance with previous observations (De Cock and Merizian, 1992). The orbital cysts were described as dermoid cysts (Tambe et al, 2003), orbital encephalocele (Moog et al, 1997), cysts with neuroepithelial hamartous structure (Bleeker-Wagemakers et al, 1990), cyst wall formed by neuroepithelium and glial tissues (De Cock and Merizian, 1992), vestigeal epithelial tissues of the retina (Dolfus et al, 1968), harmartomous with primitive glial and neuroepithelial structures (Wilson et al, 1985), hamartoma (Delleman and Oorthuys, 1981) or have not been specified. Based on the MR signal properties of the cyst in the present case a dermoid could be excluded.…”
Section: Discussionsupporting
confidence: 88%
“…A variety of associated malformations including cleft palate (Table 1), cardiac and costo-vertebral anomalies (Delleman et al, 1984;Scholz et al, 1999;Cambiaghi et al, 2000) (Table 1) have been reported, but were absent in our case.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Three years later, they confirmed the existence of a definitive syndrome, together with co-workers, by reporting two additional patients (Delleman et al 1984). Review of the literature reveals, to date, a total of 23 patients with features consistent with a diagnosis of OCC syndrome (Ladenheim & Metrick 1956, Renard et al 1964, Dollfus et al 1968, Delleman & Oorthuys 1981, Delleman et al 1984, Wilson et al 1985, Al-Gazali et al 1988, Giorgi et al 1989, Brodsky et al 1990, Clericuzio 1990, Hennekam et al 1990, Lauras et al 1990, Hoo et al 1991, DeCock & Merizian 1992, Moog et al 1996, Narbay et al 1996, Naumchik et al 1996. This list includes some cases which have been published in the ophthalmic literature under other headings and considers only those in which there is sufficient documentation to establish a diagnosis of OCC syndrome.…”
mentioning
confidence: 86%
“…In 1981, Delleman & Oorthuys pointed out the significance of this collection of features in a report of two patients with ocular cysts, multiple intracranial fluid filled spaces, accessory facial skin tags and defects and a variety of additional problems. They suggested a new "Oculo-cerebro-cutaneous entity" be used to designate this group of defects (Delleman & Oorthuys 1981).…”
mentioning
confidence: 99%